2018
DOI: 10.1139/cjp-2017-0884
|View full text |Cite
|
Sign up to set email alerts
|

Accelerating cosmologies with nonlinear electrodynamics

Abstract: In this paper, we consider the framework of nonlinear electrodynamics in locally rotationally symmetric (LRS) Bianchi-I universe model composed of magnetic fluid. It has been shown that an accelerated universe expansion takes place if the nonlinear electromagnetic field is a source of gravitational field. In this model, after the big bang, the universe undergoes inflation and the accelerated expansion, dissipates the initial anisotropy of the curvature part without using a selected initial condition. Further v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 64 publications
0
2
0
Order By: Relevance
“…From thermodynamics point of view in cosmological scenario, the enveloping surface should be apparent horizon and not the event horizon [74]. Apparent horizon as universe's boundary have been used in literature for examining the validity of GSLT in different cosmological set-ups [19,23,25,52,55,57,61,73,74]. In flat-FRW universe, radius of apparent horizon is related with Hubble parameter as R a = 1 H .…”
Section: Horizon Thermodynamicsmentioning
confidence: 99%
See 1 more Smart Citation
“…From thermodynamics point of view in cosmological scenario, the enveloping surface should be apparent horizon and not the event horizon [74]. Apparent horizon as universe's boundary have been used in literature for examining the validity of GSLT in different cosmological set-ups [19,23,25,52,55,57,61,73,74]. In flat-FRW universe, radius of apparent horizon is related with Hubble parameter as R a = 1 H .…”
Section: Horizon Thermodynamicsmentioning
confidence: 99%
“…Eling et al [45] demonstrated that by using terms other than Einstein-Hilbert action, one may produce entropy due to the non-equilibrium thermodynamical aspects of generalized f (R) theory [46]. By using field equations and applying thermodynamical laws to cosmological horizon, one can find rate of total horizon entropy in different gravitational setups [12,15,19,23,[47][48][49][50][51][52][53][54][55][56][57]. The behaviour of expanding universe have also been studied extensively from the thermodynamic point of view.…”
Section: Introductionmentioning
confidence: 99%